Critical Success Factors to Develop an Innovative Learning-Cluster: Empirical Analysis of Footwear Industrial Cluster in East Java - Prihadyanti, Dian (Jurnal Manajemen Teknologi, 2017)
Abstract. Cluster approach has attracted discussion among scientists and has been widely used for economic development today. Various studies have shown that clusters can provide economic benefits and become source of economic growth. Many literatures have studied about cluster, but there is still necessity in identifying factors to develop an innovative learning-cluster. This paper proposes the critical success factor to develop an innovative learning-cluster. Through case study in a footwear cluster in Indonesia, it is found that several categories are not sufficient and needs to be strengthened. General preconditions become the foundation or the initial base, while networks & partnership, institutional capacity, and market & infrastructure for learning become the boosting factor. This indicates that there is a process which has to be passed to develop an innovative learning-cluster and it cannot directly be created from its establishment. For footwear cluster, technical skill and knowledge of human resources, particularly designer and marketing personel becomes key factor for learning to achieve innovation. Government policy becomes a limiting factor to form an innovative learning-cluster. Leadership factors also plays important role to direct strategic vision for the cluster.Keywords: Innovative learning-cluster, success factors, innovation capacity, innovation performance, cluster developmentAbstrak. Pendekatan kluster telah menjadi bahan diskusi bagi peneliti dan saat ini telah banyak diterapkan dalam rangka pengembangan ekonomi. Berbagai studi telah menunjukkan bahwa kluster dapat memberikan manfaat ekonomi serta menjadi sumber pertumbuhan ekonomi. Berbagai literatur mengenai kluster telah banyak berkembang, akan tetapi masih terdapat kebutuhan untuk mengidentifikasi faktor-faktor untuk membangun sebuah innovative learning-cluster. Tulisan ini berupaya mengemukakan faktor-faktor penentu kesuksesan bagi pengembangan sebuah learning-cluster yang inovatif. Melalui studi kasus pada kluster industri alas kaki di Indonesia, diperoleh temuan bahwa beberapa kategori faktor tidaklah cukup dan masih perlu diperkuat untuk membentuk suatu learning-cluster yang inovatif. General preconditions menjadi dasar atau basis awal pengembangannya, sementara networks & partnership, institutional capacity, serta market & infrastructure untuk pembelajaran menjadi boosting factors. Hal tersebut mengindikasikan bahwa terdapat proses yang harus dilewati untuk mengembangkan sebuah innovative learning-cluster, serta tidak dapat langsung diciptakan sejak awal pendiriannya. Untuk kluster alas kaki, technical skill dan knowledge yang dimiliki sumberdaya manusia khususnya desainer dan personel pemasaran menjadi faktor kunci bagi pembelajaran untuk menghasilkan inovasi. Kebijakan pemerintah menjadi limiting factor untuk membentuk learning-cluster yang inovatif. Sementara itu, faktor kepemimpinan juga memegang peranan penting bagi visi stratejik pengembangan kluster.Keywords: Innovative learning-cluster, faktor penentu kesuksesan, kapasitas inovasi, innovation performance, pengembangan kluster